Infantile systemic hyalinosis: A case report and review of literature - Bhushan Madke; Vidya Kharkar; Sunanda Mahajan; Siddhi Chikhalkar; Uday Khopkar (Wolters Kluwer Medknow Publications, 2010)
We report a case of infantile systemic hyalinosis in a 3.5-month-old male child born out of consanguineous marriage. He presented with multiple brownish raised lesions over bony prominences. He had also developed difficulty in movement of limbs and as a result developed severe flexion joint contractures. There was history of similar complaints in elder sibling who died at the age of 5 months due to repeated episodes of pneumonia. Skin biopsy from one of the papulonodular lesions showed increased amount of amorphous hyaline matrix, which was Periodic Acid Schiff positive with scattered fibroblasts. Though classical, we report this case for its rarity in western India.